2012
DOI: 10.1684/ecn.2012.0311
|View full text |Cite
|
Sign up to set email alerts
|

A proliferation-inducing ligand (APRIL) in neutrophils of patients with oral cavity squamous cell carcinoma

Abstract: Available data indicating a role for neutrophils in the tumor-host reactions are controversial. In 37 patients with oral cavity squamous cell carcinoma (OSCC), we investigated the expression of a tumor-promoting, proliferation-inducing ligand (APRIL) molecule by peripheral blood neutrophils isolated from blood samples collected at presentation and three weeks after surgery, and the serum levels of TGF-␤ in the same samples. Additionally, we investigated the consequences of TLR4 activation by LPS for the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In agreement with previous studies showing that TNFSF13 is expressed by infiltrating neutrophils in solid tumors 39,40 and by myeloid BM cells in multiple myeloma, 41,42 we found that TNFSF13 was secreted by CD11b + Gr-1 + myeloid cells but not by the corresponding murine AML cells. This finding suggests that mature myeloid BM cells support AML cells by secreting TNFSF13.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies showing that TNFSF13 is expressed by infiltrating neutrophils in solid tumors 39,40 and by myeloid BM cells in multiple myeloma, 41,42 we found that TNFSF13 was secreted by CD11b + Gr-1 + myeloid cells but not by the corresponding murine AML cells. This finding suggests that mature myeloid BM cells support AML cells by secreting TNFSF13.…”
Section: Discussionsupporting
confidence: 93%
“…Pro-neoplastic properties of the N2 phenotype cells are associated with the production of proangiogenic and growth factors (e.g., VEGF: vascular endothelial growth factor), as well as enzymes degrading the extracellular matrix (e.g., MMP-9: matrix metalloproteinase 9). It is also believed that TANs/N2 are capable of inhibiting the immune response against cancer cells by influencing the activity of other cells (Jabłońska et al 2012 ; Schmielau and Finn 2001 ; Tazawa et al 2003 ).…”
Section: Neutrophil Heterogeneity In the Neoplastic Processmentioning
confidence: 99%
“…Studies Cancer biomarker Neutrophil infiltration [26] OSCC [27] OSCC-tongue NLR [28] HNSCC [29] HNSCC [30] OSCC Neutrophil-secreted proteins [31] OSCC [32] OSCC-tongue [33] OSCC [34] OSCC [35] OSCC [36] OSCC [37] OSCC ROS [38] Review [39] OSCC [40] OSCC Cancer microenvironment MMPs [41] HNSCC [42] HNSCC [43] Fibrosarcoma [44] Cervical Angiogenesis [45] Fibrosarcoma [46] Pancreatic ductal adenocarcinoma [47] Fibrosarcoma Prostate NETs [48] Lung [22] Liver Microbiome, neutrophils, and cancer [49] OSCC [50] OSCC [51] OSCC-gingival [52] Colorectal [53] HNSCC [54] HNSCC Modulation of cell function and signaling [55] Orohypopharingeal [56] HNSCC [57] HNSCC [58] Multiple tumors [26] OSCC [59] Chronic myelogenous leukemia…”
Section: Rolementioning
confidence: 99%
“…Members of the TNF superfamily of secreted proteins, including APRIL [35], TRAIL, and DR5 [36], were also investigated as possible oral cancer biomarkers. APRIL has been shown to regulate tumor cell survival and proliferation through binding to heparin sulfate side-chains of proteoglycans or to the calcium modulator and cyclophilin ligand interactor [65].…”
Section: Neutrophil-secreted Proteinsmentioning
confidence: 99%